Orchestral Conducting in the Nineteenth Century - Illiano, Roberto; Niccolai, Michela (Turnhout Brepols, 2014)
The nineteenth century witnessed the birth of the public figure of the orchestral conductor. Like composers and performers, orchestral conductors registered the transformed concept of the ‘musical work’. Whilst the Industrial Revolution generated new types of profession, the orchestral conductor’s career emerged, as an outcome of the greater consideration that was devoted to the act of ‘performance’. In the present volume nineteen scholars explore historical and sociological phenomena connected to the nineteenth-century system of performance and musical production in which the orchestral conductor worked. A number of chapters investigate the musical performances of famous orchestral conductors; conducting by renowned composers (including Berlioz, Bottesini, Charpentier, Liszt, Mendelssohn, Paganini and Rolla) and orchestral treatises for military bands. The authors featured are: Fabrizio Ammetto, Maria Teresa Arfini, Rémy Campos, Paola Cannas, Antonio Carlini, Claudia Colombati, Mariateresa Dellaborra, Gilles Demonet, Elisa Grossato, Emmanuel Hervé, Étienne Jardin, Walter Kurt Kreyszig, Naomi Matsumoto, Michela Niccolai, Fiona M. Palmer, Rudolf Rasch, Renato Ricco, Gesine Schröder, Ruben Vernazza.
Keywords: 19th Century (1801-1900); Conducting; Orchestra; Music history